Bioprospecting of pharmacological potentials of 7-hydroxycitronellal monoterpene: In silico approach - Silva, Marcus Antônio Bezerra da (2017)
Essential oils of plants, as well as compounds derived from these oils like terpenes, have attracted increasing interest because of their antioxidant properties. 7-hydroxycytronelal is a monoterpene derived from citronellal, presenting molecular formula C10H20O2. Aimed evaluate the in silico pharmacological activities of monoterpene, among them the antioxidant activity. For this, in silico techniques were used through the program PASS™ online, for evaluation of the theoretical pharmacological properties of the substance. The results showed a broad spectrum of pharmacological activities in silico, among them antioxidant effect.. Thus concluded that monoterpene has antioxidant activity theoretical in silico. However, more in vitro and in vivo studies should be performed to corroborate these activities.